HISTORICAL CHARACTERISTICS OF CHEMICAL EYE INJURIES - Matovic, Marija; Janicijevic, Katarina; Janicijevic Petrovic, Mirjana (PONS - medicinski časopis, 2016)
Introduction Chemical eye injuries are described as trauma of the eye which represent an urgent state in ophthalmology, and are mostly localized on the anterior segment. Causes of injuries are acid, alkali, mixed and non identified agents. Diagnostic procedures are easy, but therapy is complex. Aim - to describe the historical characteristics of chemical eye trauma and analyze the causes as the most common agents involved in chemical injuries at tertiary level of referent region. Material/Methods The retrospective study conducted on data of the chemical eye injuries presented at Clinic of ophthalmology in Clinical Centre of Kragujevac (Central Serbia) in past three years. One hundred and thirteen patients (164 eyes) who were presented from September, 2013 to September, 2015 for observation with chemical eye injuries were included in this study. Authors analyzed and showed the most important of hystorical characteristics: gender, age, categories of chemical agents and location of the accident. Results Males were more often reported with injures than females (66.37% vs. 33.63%). The mean age across categories was 46-60 years (54, 47.79%). The most common categories of chemical agents: hydrochloric acid – 42 eyes (25.61%), acetic acid – 37 eyes (22.56%), quicklime – 37 eyes (22.56%), quenched – 24 eyes (14.63%) and mixed – 24 eyes (14.63%). The location where injury occurred was mostly at home – 84 eyes (51.22%) and et work – 80 eyes (48.78%). Conclusion Correlation of references from this study and world references in the medium urban countries with dominators light industries was developed to be relatively identical. In frequency from this study allocated by chemical eye injury – males dominated professionally in social and private industry sector while it was dominated by female in households while maintaining general hygiene. Frequently bases were quenched and quicklime. The most common location was inside the home. Keywords: history characteristics, chemical eye injuries, categories of agent, urban countries, location of injuries